Community Participation in the Development of Sustainable Agriculture Based on Coffee Plantations in Kalibaru District, Banyuwangi - Pribadi, Titanio; Mukhoyyaroh, Naila Izzatul; Naim, Abu; Bintoro, Wahyu A.; Setiawan, Sigit Edy (Graduate School, Universitas Brawijaya, 2024)
Coffee plants are a factor in Indonesia's economic growth which implements an agroforestry system. Agroforestry systems and management emphasize effective agricultural systems and consider conservation of natural resources. This research aims to analyze the supporting factors for sustainable agriculture based on coffee plantations, community perceptions in developing sustainable agriculture, and community strategies for sustainable agricultural development in Kalibaru District. The research method uses quantitaive descriptive research with collection methods in the form of observation, inventory and interviews. The data analysis method is in the form of likert scale analysis and SWOT analysis. The study suggests that some communities have already understood the concept of agroforestry with a perception index found under about > 50% of the value-rating category. It deals with the influential aspects of sustainable agricultural development strategies is the natural resource of coffee plantations and community knowledge of sustainable agriculture. However, coffee community knowledge resources with a 67% education percentage in senior high schools, so that knowledge about sustainable agriculture requires moderate help and education for communities. Strategies that can be used to improve sustainable agriculture in Kalibaru District are to increase assistance and education to the community about environmentally friendly sustainable agriculture and the preservation of the agroforestry system in coffee plantations in Kalibaru District.